2000
DOI: 10.1021/jf000549h
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Flavan-3-ols in Spanish Foodstuffs and Beverages

Abstract: An HPLC method, using detection after postcolumn derivatization with p-dimethylaminocynnamaldehyde (DMACA), was developed for the quantitative analysis of individual flavanols in food. This method was applied to flavanol determination in 56 different kinds of Spanish food products, including fruit, vegetables, legumes, beverages (cider, coffee, beer, tea, and wine), and chocolate. The determined compounds corresponded to the catechins and proanthocyanidin dimers and trimers usually present in food and, therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
243
9
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(297 citation statements)
references
References 26 publications
37
243
9
8
Order By: Relevance
“…Epicatechin was the most abundant fl avan-3-ol monomer in raspberry, blackberry, cherry and apple wines, while catechin was predominant in the raspberry wine. The quantitative analysis of fl avan-3-ols in Spanish (41) and Dutch (42) food products showed the identical relation between catehin and epicatechin in the raw fruits specifi ed above. The sum of fl avan-3-ols determined in this work in fruit wines decreased in the order: raspberry, blackberry, apple, cherry and strawberry.…”
Section: Individual Phenolic Compounds Of Fruit Winesmentioning
confidence: 76%
“…Epicatechin was the most abundant fl avan-3-ol monomer in raspberry, blackberry, cherry and apple wines, while catechin was predominant in the raspberry wine. The quantitative analysis of fl avan-3-ols in Spanish (41) and Dutch (42) food products showed the identical relation between catehin and epicatechin in the raw fruits specifi ed above. The sum of fl avan-3-ols determined in this work in fruit wines decreased in the order: raspberry, blackberry, apple, cherry and strawberry.…”
Section: Individual Phenolic Compounds Of Fruit Winesmentioning
confidence: 76%
“…Generally, tannins in certain fruits serve as a natural defense mechanism against microbial infections [134]. The mechanisms of anti-bacterial activity of tannins have been described [147]. Likewise, proanthocyanidin polymers from D. kaki fruit exhibit anti-fungal properties as well as protective effect against diabetic oxidative stress with hyperlipidemia and anti-cancer activities [142,148,149].…”
Section: Tanninsmentioning
confidence: 99%
“…Several studies demonstrated that the potential health benefits of fruits and vegetables could be partially attributed to their polyphenol contents, in particular, flavonoids [8,41]. Fruits and vegetables are considered an important source of dietary flavonoids in addition to a number of potentially bioactive components such as fiber, folate, antioxidant vitamins, and potassium [56,57].…”
Section: Fruits and Vegetablesmentioning
confidence: 99%